1985
DOI: 10.1111/j.1399-6576.1985.tb02262.x
|View full text |Cite
|
Sign up to set email alerts
|

Buprenorphine Delays Drug Absorption and Gastric Emptying in Man

Abstract: The aim of the present study was to investigate the effects of buprenorphine on drug absorption and gastric emptying in man, using paracetamol absorption as an index of gastric emptying rate. Paracetamol was given to eight healthy volunteers p.o. together with or without a single i.v. dose of buprenorphine 4 micrograms kg-1 body weight. Nausea occurred in five of the subjects, four subjects vomited and one was excluded due to vomiting during the study period. The mean peak serum paracetamol concentration (Cmax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

1987
1987
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…Finally, opioid-induced vomiting may be partially explained by delayed gastric emptying (see section 3.2) as proven for morphine (Todd & Nimmo 1983) or buprenorphine (Adelhoj et al 1985).…”
Section: Nausea and Vomitingmentioning
confidence: 98%
“…Finally, opioid-induced vomiting may be partially explained by delayed gastric emptying (see section 3.2) as proven for morphine (Todd & Nimmo 1983) or buprenorphine (Adelhoj et al 1985).…”
Section: Nausea and Vomitingmentioning
confidence: 98%
“…Published clinical trials demonstrated that buprenorphine delays gastric emptying in humans (Adelhoj, Petring, Ibsen, Brynnum, & Poulsen, 1985;Trotter, Rowbotham, Windram, & Mushambi, 1991). Product information on methadone and LAAM indicate the same (Prod Info Methadone HCL, 1996;Prod Info Orlaam, 2000).…”
Section: Discussionmentioning
confidence: 95%
“…It is known to cause ileus and constipation but has not been described previously to cause clinical gastroparesis. Two studies have looked specifically at buprenorphine's effect on gastric emptying [5,6]. Both studies found prolonged gastric emptying in healthy volunteers, providing proof of the concept that buprenorphine was the probable cause of this patient's gastroparesis.…”
Section: Discussionmentioning
confidence: 98%